Produção otimizada e caracterização de bloco sílico-calcário utilizando rejeito de mineração de carvão in natura - Silva, Rogério Barbosa da (2022)
The aim of this research was the characterization of specimens of sand-lime bricks (slb) using in natura coal mining tailings to replace natural sand, using the Mixture Experiment technique to optimize proportions between the raw materials that maximize the compressive strength of the specimens produced. The research was carried out initially by producing specimens with proportions between the raw materials that were chosen through Mixture Experiments technique só that a response surface model was obtained capable of optimizing proportions that maximize the compressive strength of new specimens produced. The characterization of the raw materials was carried out by: Granulometry, X-Ray Fluorescence (XRF), X-Ray Diffraction, Thermal Analysis (TA) and Total Sulfur, for the specimens initially produced were: Compressive strength, XRD, TA and Scanning Electron Microscopy with EDS (SEM-EDS). Analysis of Variance (ANOVA) and Tukey test were used to assess the statistical significance of the variables. The specimens optimized by the model were characterized by compressive strength test, XRD, TA, SEM-EDS, Water Absorption, Linear Shrinkage, Apparently Density and Accelerated aging test evaluating the compressive strength, leaching and solubilization. For the specimens initially produced, compressive strengths between 4.99MPa to 19.26 MPa were obtained. Statistical analyzes showed that hydrated lime is the variable that most contributes to the increase in strength and the tailings that most contribute to the decrease in compressive strength. The response surface model obtained was satisfactory for prediction and optimization studies for proportions that present at least 15% sand and up to 76% tailings, showing that the proportion that maximizes compressive strength is obtained with 90% sand and 10% hydrated lime. The specimens produced with an optimized proportion showed water absorption between 14.75% and 16.22%, apparently density between 1894 kg/m³ and 1922 kg/m³, without retraction or expansion of their measures. The accelerated aging test showed that the climatic conditions simulated did not affect the compressive strength, however it increased the leached amounts of some metals and increased the solubilization at levels that suggest that the specimens can act as stabilizers/solidifiers of these analyzed metals, the high sulfate solubilization suggests that the future bricks can be used in unsaturated condition. Finally, the tailings showed potential to be used in the manufacture of slb to replace natural sand.